2012
DOI: 10.3346/jkms.2012.27.12.1472
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Korean Red Ginseng for Acute Respiratory Illness: A Randomized and Double-Blind Clinical Trial

Abstract: Korean Red Ginseng (KRG) is a functional food and has been well known for keeping good health due to its anti-fatigue and immunomodulating activities. However, there is no data on Korean red ginseng for its preventive activity against acute respiratory illness (ARI). The study was conducted in a randomized, double-blinded, placebo-controlled trial in healthy volunteers (Clinical Trial Number: NCT01478009). Our primary efficacy end point was the number of ARI reported and secondary efficacy end point was severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…More recent clinical studies reported beneficial effects of P. ginseng and P. quinquefolius in preventing infections of the upper respiratory tract. In a randomized, double-blind, placebocontrolled trial involving 100 healthy volunteers, Lee et al (2012) reported that Korean red ginseng (3 g/day per os for 12 weeks) significantly reduced the episodes of acute respiratory illness (ARI), mainly due to rhinovirus and coronavirus infections, in the 50 subjects randomized in the treatment arm with respect to the 50 individuals in the control group. A patented poly-furanosylpyranosyl-saccharide-rich extract of P. quinquefolius, COLD-fX, showed a beneficial effect on common cold.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…More recent clinical studies reported beneficial effects of P. ginseng and P. quinquefolius in preventing infections of the upper respiratory tract. In a randomized, double-blind, placebocontrolled trial involving 100 healthy volunteers, Lee et al (2012) reported that Korean red ginseng (3 g/day per os for 12 weeks) significantly reduced the episodes of acute respiratory illness (ARI), mainly due to rhinovirus and coronavirus infections, in the 50 subjects randomized in the treatment arm with respect to the 50 individuals in the control group. A patented poly-furanosylpyranosyl-saccharide-rich extract of P. quinquefolius, COLD-fX, showed a beneficial effect on common cold.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Red Ginseng (RG) is a well-known herbal medicine with anticancer, antiallergy, anti-inflammatory and anti-fatigue effects. [21][22][23] A recent clinical study confirmed its protective effect on acute respiratory tract infections, 24) and oral administration of RG extract prior to influenza A virus infection was shown to increase survival in a mouse model. 25) Not only dietary RG extract but also components of the extract such as polysaccharides and saponin have been reported to increase protection against influenza A virus infection.…”
Section: Evaluation Of In Vitro Activity Of Xylitol Against Hrsvmentioning
confidence: 99%
“…Adverse events such as voice disorder, ophthalmalgia, perinea pain and renal stones in the erectile dysfunction study were shown to have no relation with the test sample [ 31 ]. In a 12-week intervention study with healthy subjects, there were no statistical differences between the placebo and ginseng groups for adverse events, and specific events were not observed ( p = 0.378) [ 39 ]. The observed adverse events of gastritis, arthritis and urticaria during the study period had no causal relationship to the ginseng intake [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a 12-week intervention study with healthy subjects, there were no statistical differences between the placebo and ginseng groups for adverse events, and specific events were not observed ( p = 0.378) [ 39 ]. The observed adverse events of gastritis, arthritis and urticaria during the study period had no causal relationship to the ginseng intake [ 39 ]. Vaginal bleeding was reported in the study on sexual dysfunction in menopausal females [ 30 ].…”
Section: Resultsmentioning
confidence: 99%